Impact of Corporate Governance on Financial Risk of Nepalese Commercial Banks - Dhakal, Padam; Neupane, Pragya; Joshi, Prakash; Adhikari, Radhika; Shah , Rakesh; Sunuwar, Rebika (Nepalese Journal of Finance, 2025)
The study examines the impact of corporate governance on financial risk of Nepalese commercial banks. Non-performing loan and cash reserve ratio are selected as the dependent variables. The selected independent variables are board size, audit committee, ownership structure, leverage, board independence, and foreign capital. The study is based on secondary data of 13 commercial banks with 104 observations for the period from 2015/16 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of impact of corporate governance on financial risk of Nepalese commercial banks. The study showed that board size has a negative impact on non-performing loans and cash reserve ratio. It indicates that larger the board size, lower would be the non-performing loans and cash reserve ratio. Similarly, audit committee size has a negative impact on non-performing loans and cash reserve ratio. It indicates that higher the audit committee size, lower would be the non-performing loans and cash reserve ratio. Likewise, board independence has a negative impact on non-performing loans and cash reserve ratio. It indicates that higher the board independence, lower would be the non-performing loans and cash reserve ratio. Further, foreign capital has a negative impact on non-performing loans and cash reserve ratio. It indicates that higher the foreign capital, lower would be the non performing loans and cash reserve ratio. However, leverage has a positive impact on non-performing loans and cash reserve ratio. It indicates that higher the leverage, higher would be the non-performing loans and cash reserve ratio. Likewise, ownership structure has a positive impact on non-performing loans cash reserve ratio. It indicates that higher the ownership structure, higher would be the non-performing loans and cash reserve ratio.